Metabolomics analysis in rat hearts with ischemia/reperfusion injury after diazoxide postconditioning - Xiang, Cen; Yu, Shoujia; Ren, Qiyang; Jiang, Boyi; Li, Jing; Zhang, Donghang; Wei, Yiyong (Frontiers in Molecular Biosciences, 2023)
Background: Diazoxide is a selective mitochondrial-sensitive potassium channel opening agent that has a definite effect on reducing myocardial ischemia/reperfusion injury (MIRI). However, the exact effects of diazoxide postconditioning on the myocardial metabolome remain unclear, which might contribute to the cardioprotective effects of diazoxide postconditioning. Methods: Rat hearts subjected to Langendorff perfusion were randomly assigned to the normal (Nor) group, ischemia/reperfusion (I/R) group, diazoxide (DZ) group and 5-hydroxydecanoic acid + diazoxide (5-HD + DZ) group. The heart rate (HR), left ventricular developed pressure (LVDP), left ventricular end-diastolic pressure (LVEDP), and maximum left ventricular pressure (+dp/dtmax) were recorded. The mitochondrial Flameng scores were analysed according to the ultrastructure of the ventricular myocardial tissue in the electron microscopy images. Rat hearts of each group were used to investigate the possible metabolic changes relevant to MIRI and diazoxide postconditioning. Results: The cardiac function indices in the Nor group were better than those in the other groups at the end point of reperfusion, and the HR, LVDP and +dp/dtmax of the Nor group at T2 were significantly higher than those of the other groups. Diazoxide postconditioning significantly improved cardiac function after ischaemic injury, and the HR, LVDP and +dp/dtmax of the DZ group at T2 were significantly higher than those of the I/R group, which could be abolished by 5-HD. The HR, LVDP and +dp/dtmax of the 5-HD + DZ group at T2 were significantly lower than those of the DZ group. The myocardial tissue in the Nor group was mostly intact, while it exhibited considerable damage in the I/R group. The ultrastructural integrity of the myocardium in the DZ group was higher than that in the I/R and 5-HD + DZ groups. The mitochondrial Flameng score in the Nor group was lower than that in the I/R, DZ and 5-HD + DZ groups. The mitochondrial Flameng score in the DZ group was lower than that in the I/R and 5-HD + DZ groups. Five metabolites, namely, L-glutamic acid, L-threonine, citric acid, succinate, and nicotinic acid, were suggested to be associated with the protective effects of diazoxide postconditioning on MIRI. Conclusion: Diazoxide postconditioning may improve MIRI via certain metabolic changes. This study provides resource data for future studies on metabolism relevant to diazoxide postconditioning and MIRI.